2014
DOI: 10.3349/ymj.2014.55.5.1395
|View full text |Cite
|
Sign up to set email alerts
|

Passive Skeletal Muscle Excursion after Tendon Rupture Correlates with Increased Collagen Content in Muscle

Abstract: PurposeThis study was designed to measure time-dependent changes in muscle excursion and collagen content after tenotomy, and to analyze the correlation between muscle excursion and collagen content in a rabbit model.Materials and MethodsTwenty-four rabbits underwent tenotomy of the second extensor digitorum longus (EDL) muscles on the right legs and were randomly assigned to three groups based on the period of time after tenotomy (2, 4, and 6 weeks). The second EDL muscles on left legs were used as controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Skeletal muscle was considered as a three-dimensional network structure of muscle fibers, collagen fibers embedded in an isotropic matrix [35]. From the internal to the external level, the muscle fibers are organized histologically by the surrounding connective tissues of three different properties made of collagen fibers: the endomysium surrounds individual fibers; the perimysium binds muscle fibers into fascicles and the epimysium surrounds the whole muscle [36,37].…”
Section: Collagen and The Mechanical Properties Of Pvmmentioning
confidence: 99%
“…Skeletal muscle was considered as a three-dimensional network structure of muscle fibers, collagen fibers embedded in an isotropic matrix [35]. From the internal to the external level, the muscle fibers are organized histologically by the surrounding connective tissues of three different properties made of collagen fibers: the endomysium surrounds individual fibers; the perimysium binds muscle fibers into fascicles and the epimysium surrounds the whole muscle [36,37].…”
Section: Collagen and The Mechanical Properties Of Pvmmentioning
confidence: 99%
“…We reported that muscle excursion was decreased and collagen content was increased over time after tenotomy and that collagen content was negatively correlated with passive excursion [9]. Type I, III, and IV collagen are the main subtypes of muscle collagen [10, 11].…”
Section: Introductionmentioning
confidence: 99%